Contributing factors towards ubiquitous technology use among engineering undergraduates - Sedek, Muliati; Mahmud, Rosnaini; Ab. Jalil, Habibah; Mohd Daud, Shaffee (Penerbit Universiti Teknikal Malaysia Melaka, 2012)
Education and learning are no longer restricted to the traditional face-to-face classroom settings. This is because, due to the proliferation of technology, its’ ubiquities and advancement over the years, technology has become available to students to obtain an education and support their learning. In addition, the ability to create conducive environment, facilitating conditions and supports are paramount important in ensuring an equitable provision of affordable services over ubiquitous infrastructure, especially in education. Having a conducive and supporting environment is not only the central factor that influences the use of ubiquitous technology. According to Laura (2001), personal attitude like willingness, readiness and competency can also affect learners in using technology. Therefore, this study aims to determine contributing factors that influence the usage of ubiquitous technology among engineering undergraduates either to be utilized for learning or leisure purposes. The following discussion will base on the Unified Theory of Acceptance and Use of Technology Model (UTAUT) by Venkatesh et. al (2003). The data of this study is gathered through a questionnaire, with the reliability of 0.922 for factors. The sample is undergraduates’ studying at faculty of engineering and a statistical analysis of data collected is performed by SPSS 17. Result shows that the central factor that contribute to the ubiquitous technology use is performance expectancy (mean = 3.51, SD = 0.555), followed by effort expectancy (mean = 3.35, SD = 0.505), social influence (mean = 3.11, SD = 0.545) and finally the least influenced factor is facilitating factor (mean = 2.82, SD = 0.404).